Modified method for qualitative thyroestatic substances determination in muscle tissue and urine of food producing animals and the application of Planar Thin Layer Chromatography 2D and 4x4D horizontal development. - TYRPENOU (Α.Ε.ΤΥΡΠΕΝΟΥ), A. E.; GOUTA (E.H. ΓΟΥΤΑ), E. H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Substances with thyreostatic action, also known as anti-hormones [AHs], are extracted by methanol in the presence of an internal standard. Percolation of the methanol extract through a mercurated adsorption mini-column allows a selective and reproducible extraction of the AHs by creating a specific complex with Hg ions. After elution of the Ahs with an acidic sodium chloride solution, the pH of the eluate is adjusted with buffer to 8,0 and allowed to react with NBDCl, a reagent which reacts only with thiols and amines. After reaction, the AH-NBD complexes formed are extracted in acid medium using TBME and after it has been dried down and reconstituted with TBME to the required volume, the ether fraction is spotted on to a HPTLC plate for horizontal development using sophisticated instrumentation. A cysteine water solution reacts with the AH-NBD complexes which are not fluorescent and they are converted into cystein-NBD complexes which are strongly fluorescent at 366 nm. This method, based on Verbeke R, de Brabander HF, 1984 method, has been modified in some steps concerning the mini-column preparation, the elution, the buffer replacement and chromatography step. The limit of detection no the plate, has been determined to be lower than lng by direct UV observation at 366nm, while the lower limit of detection achieved in the sample was 25 μg/kg.